The influence of match location, quality of opposition, and match status on technical performance in professional association football - Taylor, J. B.; Mellalieu, S. D.; James, N.; Shearer, D. A. (Journal of Sports Sciences, 2008)
The aim of this study was to examine the effects of match location, quality of opposition, and match status on the technical aspects of performance within a single professional British football team. Forty matches from the 2002-2003 and 2003-2004 domestic league seasons were notated post-event using a computerized notational analysis system with 13 on-the-ball behaviours and corresponding outcomes (successful or unsuccessful) assessed. Log-linear modelling procedures indicated that the incidences of all on-the-ball technical behaviours, with the exception of "set-pieces", were influenced by at least one of the three situation variables, with both independent and interactive effects found. In contrast, logit modelling suggested that there was no general influence of the situation variables on the outcomes of the on-the-ball behaviours. The findings emphasize the need for notational analysts and coaches to consider the potential independent and interactive effects of match location, quality of opposition, and match status when assessing the technical components of football performance, particularly those relating to behaviour occurrence. Future research should consider the effects of additional situation variables purported to influence the mental, physical, technical, and tactical components of football performance.